Folded interferometer to measure coherence–polarization matrix - Chandra S.; Gautam A.; Singh R.K. (My University, 2025)
We present and experimentally demonstrate a new, to the best of our knowledge, technique to quantitatively measure coherence–polarization (BCP) matrix with correlations of only two Stokes fluctuations. The BCP matrix is a square matrix with four elements that involves two-point correlations among orthogonal polarization components. A theoretical framework of the technique is developed, and its viability is demonstrated by a proof of principle experiment. Experimental tests and measurement of the elements of the BCP matrix of statistically stationary beams are demonstrated. © 2024 Optica Publishing Group.